Perceptions of condom use in Haitian migrants on the northwestern border of Mexico. - Esquivel_Rubio, Abraham Isaac; Márquez-Vega, María Aracely; Domínguez -Chávez, Claudia Jennifer; Alvarado-Pizarro, Ángel Noé; Tizoc-Márquez, Arodi (Horizonte Sanitario, 2021)
Abstrac: Objective: To identify the perceptions of condom use in Haitian migrants on the northwestern border of Mexico.Materials and methods: Qualitative ethnographic study, 7 Haitian migrants were interviewed, the information was analyzed by the NVivo program, to understand the frequency and structure of the data; later a process of categorization, interpretation and theorization of the study phenomenon was carried out.Results: From a total of 281 units of analysis, a categorization process was carried out, which allowed structuring 2 categories, 6 subcategories and 12 codes. It is identified that the use of condoms in Haitian migrants is interpreted as an element of protection to sexual health, mainly in the prevention of unplanned pregnancies; however, barriers and consequences of use are identified on a personal, cultural and religious level. The construction of the idea of ​​using it, relies on the type of relationship and level of trust that one has in the sexual partner, so being married or living in common law exempts the obligation or social commitment of using the condom. Likewise, the idea of ​​protection weakly reflects the concern about the transmission of STIs.Conclusions: The condom is perceived as an important element for the prevention of unplanned pregnancies and HIV, it does not refer to constant condom use, therefore the development of culturally adapted interventions is recommended to increase the use of condoms and HIV prevention in Haitian migrants in the context of the northern border of Mexico.Keywords: Emigrants and Immigrants; Condom; Sexually Transmitted Diseases; HIV.